Ni, Cr and Co Phytoremediations by Alyssum murale Grown in the Serpentine Soils Around Guleman Cr Deposits, Elazig Turkey - Konakci, Nevin; Kislioglu, Merve Sasmaz; Sasmaz, Ahmet (Springer, 2023)
Serpentine soils containing high levels of nickel and other metals are particularly preferred by some plants that accumulate nickel in their bodies. In this study, the Ni, Co, and Cr accumulation capacities of A. murale grown in Guleman's serpentine soils were measured. In this respect, 12 A. murale and their soils were collected from the mining site and surroundings. Afterwards, the collected samples were measured in order to evaluate the translocation and accumulation amounts of Ni, Cr, and Co. For that, soil and plant samples were analyzed using inductively coupled plasma mass spectroscopy (ICP-MS). The mean Ni concentrations in the soil, roots, and shoots of A. murale were measured as 2475, 7384, and 7694 mg/kg, respectively. The mean Cr concentrations in the soil, roots, and shoots of A. murale were measured as 742, 33, and 8.4 mg/kg while the mean Co concentrations of A. murale in the soil, roots, and shoots were 166, 10.2, and 23.5 mg/kg, respectively. Then, ECR and ECS values were calculated for Ni, Co, and Cr. The results indicated that A. murale grown in Guleman's serpentine soils may be helpful for the rehabilitation studies of mining soils contaminated by Ni and can be utilized for phytoextraction.
Keywords: Phytoremediation; Alyssum murale; Guleman mining area; Accumulation; Serpentine soil